DEVELOPING AN IT INFRASTRUCTURE MODEL FOR ENHANCING DIGITAL LITERACY THROUGH WEB-BASED LEARNING: A COMPREHENSIVE FRAMEWORK - Feri Sulianta; Fitrah Rumaisa; Yan Puspitarani; Sriyani Violina; Ai Rosita (Program Studi Teknik Informatika Universitas Khairun, 2024)
In today's rapidly evolving educational landscape, there is a growing need to develop an IT infrastructure model that can effectively support web-based learning environments to enhance digital literacy. The proposed model offers a comprehensive framework for educational institutions to integrate digital technologies into their curricula seamlessly. Key elements of the model include essential hardware, user-friendly software, and advanced security measures, each playing a vital role in creating a seamless, secure, and efficient digital learning experience. This study explores the dynamic interactions among these components and their collective influence on fostering a conducive and productive web-based learning environment. By addressing the need for reliable infrastructure, scalable solutions, and robust security protocols, the model provides a holistic approach to improving digital literacy in educational contexts. The research underscores the critical role of a well-structured IT infrastructure in supporting digital education, offering actionable insights and recommendations for implementation. Moreover, it emphasizes that a well-developed IT infrastructure is foundational for the long-term success of web-based learning programs, enabling institutions to meet diverse learner needs, adapt to technological advances, and ensure sustainability in the digital education landscape.